Modal Utama Agar Menjadi Guru Favorit Bagi Peserta Didiknya - Yazidul Busthomi (STIT Muhammadiyah Paciran Lamongan, 2019)
Abstract: Being a teacher is a truly noble job. He is responsible not only to make the intelligent human beings in the field of science, but also good moral in this life. A human child who at first did not understand anything, in the presence of a teacher educated to understand life better and get to know the world. On the shoulders there are tasks and responsibilities for the future of a smarter and more intelligent generation. So noble work of a teacher as well as how heavy the duties and responsibilities of being a teacher. This is why not everyone can be a successful teacher. Only certain people who have a sense of love for children or learners and dedicated to the world of education are able to become a teacher. This is the person of a teacher who successfully teaches and educates in front of his students, the figure of a favorite teacher loved by his protege. The main capital to be a favorite teacher for students that is as follows: 1. Close to students, 2. Build a fun atmosphere, 3. Can play as a second parent, 4. Become a friend in learning, 5. Personality worth imitating, 6. Be affectionate, 7. Patience in teaching, 8. Not arrogant.